The Sociology of Development: Community Participation and Social Change - Viola Febritiyasya; Wila Armanda; Ibnu Fajri; Akdila Bulanov (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article discusses sociological development, participatory development,and the relationship between development and social change in community life. The purpose of this research is to understand the development process and its impact on social, cultural, and lifestyle changes. The method used in this research is a qualitative descriptive approach through a literature review, collecting data from various sources such as books and scientific journals. The results show that development does not only focus on economic growth but also influences changes in values, norms, behavior, and social structures. Futhermore, community participation is a crucial factor in the success of development because communities play a direct role in the planning, implementation, and monitoring of development. Development also drives social change towards a more modern and prosperous society. Thus, sociological development plays a crucial role in understanding the relationship between development and social change so that development can proceed fairly, equitably, and improve community welfare.